Kearifan Lokal Sebagai Implementasi P5 Pada Kurikukulum Merdeka di SMK Negeri 1 Cilegon - Fredy Kusuma Nugraha; Naufal Taufiqul Hakim; Maya Saralina; Ilham Akbar Darmawan; Ngadiana Ngadiana (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This research focuses on the performance of local wisdom works commemorating the birthday of the Prophet Muhammad SAW as a form of implementing the Pancasila Student Profile Strengthening Project (P5) which aims to preserve and introduce traditions and culture in Banten to students at SMK Negeri 1 Cilegon which has implemented the independent curriculum Study. This research uses qualitative methods with data collection in the form of observations, interviews and documentation. The results of this research are the high enthusiasm of students at SMK Negeri 1 Cilegon in celebrating the birthday of the Prophet Muhammad SAW at school.